A.A.V.V.: Reason, morality, and law. The philosophy of John Finnis, J. Keown & R.P. George (eds.), Oxford, Oxford University Press, 2013, 616 pp. - Massini Correas, Carlos I. (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2013)

(untitled)
Fil: Massini Correas, Carlos I.. Universidad de Mendoza